Gallbladder Stones: Oral Dissolution Therapy - Johnson L Thistle (Canadian Journal of Gastroenterology)
Chenodiol is noninvasive, safe and moderately expensive. Because of diarrhea, the need for aminotransferase monitoring, the long duration of therapy required, and the minority of patients who are appropriate candidates, it has had limited use. Ursodiol is generally preferred because it has minimal side effects. Patients with increased surgical risk, mild to moderate symptoms, and gallstones which are either floatable with oral radiopaque contrast media or radiolucent by computed tomography scan in a nonobstructed gallbladder arc appropriate candidates for oral bile acid therapy. Silent stones should not be treated under most circumstances.